1999
DOI: 10.1053/cp.1999.v66.100038001
|View full text |Cite
|
Sign up to set email alerts
|

Propofol decreases the clearance of midazolam by inhibiting CYP3A4: An in vivo and in vitro study

Abstract: Propofol decreases the clearance of midazolam, and the possible mechanism is the competitive inhibition of hepatic CYP3A4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…It has recently been shown that lidocaine is metabolized by multiple hepatic CYP isoenzymes; CYP1A2 and 3A4 in humans [6], and 3A2 and 2B1 in the rats [10]. Propofol is also metabolized by 3A4 and 2B6 in humans [3,5] and by CYP1A2 and 2B1 in rats [2]. The rats possess CYP 3A2 as a homolog of 3A4 [9], instead of genuine 3A4 [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been shown that lidocaine is metabolized by multiple hepatic CYP isoenzymes; CYP1A2 and 3A4 in humans [6], and 3A2 and 2B1 in the rats [10]. Propofol is also metabolized by 3A4 and 2B6 in humans [3,5] and by CYP1A2 and 2B1 in rats [2]. The rats possess CYP 3A2 as a homolog of 3A4 [9], instead of genuine 3A4 [11].…”
Section: Discussionmentioning
confidence: 99%
“…Drug metabolism generally occurs through hydroxylation and glucuronidation in the liver CYP system [3,4]. It was recently shown that the metabolism of propofol can be mediated by multiple hepatic CYP isoenzymes including CYP1A2 [2] and CYP3A4 [5]. The local anesthetic lidocaine can also be metabolized by CYP1A2 and CYP3A4 [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that CYP3A4 inhibitors such as ketoconazole, ritonavir and others can significantly inhibit midazolam metabolism leading to a several hundred times longer half-life (Ahonen et al 1999;Hamaoka et al 1999;Oda et al 1999;Wang et al 1999Wang et al , 2000Kanazu et al 2005;Vossen et al 2007;Sugiyama et al 2011). The interand intraindividual expression of CYP3A4 is highly variable (as much as 40-fold) in humans (Wojnowski 2004).…”
Section: Piperidinedione Derivativesmentioning
confidence: 99%
“…It was recently reported that propofol modified the activity of multiple hepatic CYP isozymes [1,2] including CYP1A2 [3] and CYP3A4 [4]. Additionally, propofol has been shown to inhibit the metabolism of such drugs [4,5].…”
mentioning
confidence: 99%